Seberapa Besar Pengaruh Konsumsi Daging Sapi di Kota Jambi Periode 2005-2019? - Abd Haris; Trie Hierdawati; Amrizal Amrizal; Rian Dani (Universitas Batanghari Jambi, 2022)
This study aims to determine the factors that influence beef consumption and to find out how the factors influence beef consumption in Jambi City for the period 2005-2019. The type of data used in this study is Time Series data which is cumulative, namely data in the form of numbers, and the source of the data obtained is secondary data, namely data sourced from Jambi City Financial Statistics for the period 2005-2019. The data used are consumption expenditure data for 2005-2019, per capita income data for 2005-2019, data on prices for 2005-2019 and Jambi City's Inflation Development for 2005-2019. The results of this study indicate that the quality of livestock breeds has little effect on meat consumption in Jambi City. The percentage growth of average per capita income is 13.84%, the average inflation rate is 11.74%, and the development of beef consumption is 4.92% on average. From the results of the regression on the level of public consumption has R2 = 0.934 or 93.4 percent. This shows that the contribution of the independent variable consists of income per capita (X1), beef prices (X2) and inflation (X3) to the dependent variable, namely the level of public consumption (Y) of 93.4% while 6.6% is influenced or explained by other variables.